How health system failures and prevailing social norms drive mistreatment of women in maternity care in Ethiopia: a qualitative study - Habtamu Kasaye; Vanessa Scarf; Annabel Sheehy; Kathleen Baird (Global Health Action)
Background Mistreatment of women during maternity care is a widespread global issue, particularly in low- and middle-income countries where health disparities intersect with rigid gender norms, systemic inequality and domestic violence. Objectives This paper aims to explore how health system failures and societal norms against women contribute to the mistreatment of women during maternity care. Methods A qualitative study was conducted among maternal healthcare providers in the East Wollega Zone, Ethiopia. In-depth interviews with purposively selected participants in Afan Oromo, each lasting 30–60 min, were conducted until data saturation was reached at 20 interviews. The interviews were audio-recorded, transcribed, translated into English, coded using NVivo 12 and analysed through thematic analysis guided by the Socioecological and Quality of Care frameworks. Results Health system conditions and constraints, such as under-resourcing and issues related to governance and providers’ prejudices shaped by societal norms, were found to drive mistreatment of women during maternity care. These drivers manifest at various levels throughout the healthcare system, including personal, interpersonal, facility-level, health system and societal dimensions. Overcrowding, staff shortages and low pay led to burnout, which eventually resulted in mistreatment of women. The lack of recognition from administrators and professional hierarchies also added to provider frustration, which was sometimes directed at women. Societal issues, like gender-based violence, further influenced these behaviours. Conclusion Mistreatment of women during maternity care continues to hinder the delivery of quality care. Addressing gender inequality, boosting healthcare worker motivation and ensuring fair treatment among staff are essential for promoting respectful maternity care.